Methylation-based smoking signatures in blood and tissue samples for the prediction of self-reported smoking status and mortality in patients with colorectal cancer - Yuan, Tanwei; Tagscherer, Katrin E.; Roth, Wilfried; Bewerunge-Hudler, Melanie; Brobeil, Alexander; Kloor, Matthias; Bläker, Hendrik; Brenner, Hermann; Hoffmeister, Michael (Clinical epigenetics, 2025)
Background Smoking is a well‑established risk factor for colorectal cancer (CRC) development. However, the reli‑ability of DNA methylation‑based smoking signatures in predicting smoking status and their prognostic value in CRC remain unclear, particularly across different biological sample types. - Results Five previously validated methylation‑based smoking signatures were analyzed in 2237 CRC patients with blood‑derived DNA and 2273 patients with tumor tissue‑derived DNA. Blood‑derived signatures showed strong correlations with self‑reported smoking status, effectively differentiating current smokers from never smokers (all p < 0.0001), with excellent discriminative ability (median area under the receiver operating characteristic curve: 0.94). In contrast, tumor tissue‑derived signatures exhibited much weaker associations with smoking status. Among non‑metastatic CRC patients, blood‑derived methylation signatures were significantly associated with increased risks of all‑cause and non‑CRC‑related mortality, but not with CRC‑specific mortality. Conversely, two tumor tissue‑derived signatures demonstrated stronger associations with CRC‑specific mortality compared to blood‑derived signatures. - Conclusions Blood‑derived methylation‑based smoking signatures are robust indicators for smoking exposure and are associated with increased mortality risk among non‑metastatic CRC patients. When applied to tumor tissue, signatures showed stronger associations with CRC‑specific mortality.